Ori-Finder 2, an integrated tool to predict replication origins in the archaeal genomes - Luo, Hao; Zhang, Chun-Ting; Gao, Feng (Frontiers in Microbiology, 2014)
DNA replication is one of the most basic processes in all three domains of cellular life. With the advent of the post-genomic era, the increasing number of complete archaeal genomes has created an opportunity for exploration of the molecular mechanisms for initiating cellular DNA replication by in vivo experiments as well as in silico analysis. However, the location of replication origins (oriCs) in many sequenced archaeal genomes remains unknown. We present a web-based tool Ori-Finder 2 to predict oriCs in the archaeal genomes automatically, based on the integrated method comprising the analysis of base composition asymmetry using the Z-curve method, the distribution of Origin Recognition Boxes (ORBs) identified by FIMO tool, and the occurrence of genes frequently close to oriCs. The web server is also able to analyze the unannotated genome sequences by integrating with gene prediction pipelines and BLAST software for gene identification and function annotation. The result of the predicted oriCs is displayed as an HTML table, which offers an intuitive way to browse the result in graphical and tabular form. The software presented here is accurate for the genomes with single oriC, but it does not necessarily find all the origins of replication for the genomes with multiple oriCs. Ori-Finder 2 aims to become a useful platform for the identification and analysis of oriCs in the archaeal genomes, which would provide insight into the replication mechanisms in archaea. The web server is freely available at http://tubic.tju.edu.cn/Ori-Finder2/.